Bryozoan diversity of Cyprus (eastern Mediterranean Sea): first results from census surveys (2011–2018) - ACHILLEOS, KATERINA; JIMENEZ, CARLOS; BERNING, BJÖRN; PETROU, ANTONIS (Mediterranean Marine Science, 2020)
The Mediterranean bryozoan fauna is considered to be well studied compared to other marine areas of the world. However, in the Levantine Basin, bryozoan diversity has not yet been adequately documented. This report presents the first systematic and most comprehensive study of bryozoans sampled in Cyprus during census surveys from 2011 to 2018. The specimens were collected between 9 and 620 m depth from several habitat types (mainly soft-bottom environments but also hard natural/artificial substrata, ancient shipwrecks, a marine cave, and deep-water coral habitats) around the island by means of bottom trawls, remotely operated vehicles, and scuba diving. The surveys produced a total of 91 species, 26 of which (=28%) are new records for the Levantine Basin, and 10 (=11%) are probably new to science. Our results thus show that the diversity of bryozoans in the eastern Mediterranean Sea is still significantly underestimated.